The Affect of Return on Equity, Debt to Equity Ratio and Net Profit Margin Against Company's Stock Price - Esti Riwayati, Hedwigis; Fachrukrozie Kodri; Yohana Rutmia Dewi Br Manik (Dinasti International Journal of Economics, Finance & Accounting, 2022)
The purpose from this research is to explore on how the influence of the independent variables, namely Return On Equity, Debt To Equity Ratio, and Net Profit Margin towards the dependent variable, such as stock prices in 10 Food And Beverages companies that listed on the Indonesia Stock Exchange. The research objects which used in this research is a food and beverage company that already listed on the Indonesia Stock Exchange. The analytical method used is descriptive statistical analysis and multiple linear regression analysis. With data processing tool through the Eviews 10.0 program. The test results partially indicates that Return on Equity variable has a positive and significant affect on the stock prices from those food and beverages companies. While Debt To Equity Ratio variable has a negative and insignificant affect towards it and Net Profit Margin has a positive and insignificant affect to the share price of food and beverages companies. These research results are simultaneously shows that the Return On Equity, Debt To Equity Ratio, and Net Profit Margin variables are capable to explain stock prices on those 10 food and beverages companies listed on the Indonesia Stock Exchange.